2007
DOI: 10.1002/chin.200735227
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Chemistry and Non‐Linear Properties of Tetragonal Tungsten Bronzes Materials

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…16 The simplest ferroelectric TTB is tetragonal with similar cell dimensions to the aristotype structure but with non-centrosymmetric symmetry, point group 4mm, with P4bm the most commonly assigned space group. 17 However, orthorhombic distortions of the structure are common, typically resulting in larger supercells. The simplest such orthorhombic superstructure requires a ca.…”
Section: Introductionmentioning
confidence: 99%
“…16 The simplest ferroelectric TTB is tetragonal with similar cell dimensions to the aristotype structure but with non-centrosymmetric symmetry, point group 4mm, with P4bm the most commonly assigned space group. 17 However, orthorhombic distortions of the structure are common, typically resulting in larger supercells. The simplest such orthorhombic superstructure requires a ca.…”
Section: Introductionmentioning
confidence: 99%
“…TTB structure has the general formula of A 2 BC 2 M 5 X 15 , where X = O is anion, M = Ta is octahedral cation, and A, B and C are cations. A, B and C correspond to cationic sites with 15, 12 and 9 CN (coordination number), respectively [19]. TTB-BaTa 2 O 6 structure has the pentagonal (A) sites and the square (B) sites which are occupied or not occupied by Ba 2+ cations, while small triangular (C) sites have vacancies.…”
Section: Methodsmentioning
confidence: 99%
“…The A1 sites are 12-coordinated and defined by 8 octahedra, the four larger A2 sites are 15-coordinated and defined by 10 octahedra, while the four trigonal C-sites are 9-coordinated and defined by 6 octahedra; moreover, the BO 6 octahedra are non-equivalent (two B1 sites and eight B2 sites) - Figure 1. This rich diversity of elements which can be incorporated into the TTB structure allows for compositional tuning that has been exploited for development of new phases [13,19] ranging from ferroelectrics [20][21][22] to microwave dielectrics [23,24] and to ionic conductors [25]. During the last few years, the research dedicated to novel TTB ferroelectric and ferroelectric-related materials resurrected [15][16][17][18][19][20][21][22][26][27][28][29][30][31], with the Ba 6 FeNb 9 O 30 (BFNO) [32][33][34][35] as starting point.…”
Section: Introductionmentioning
confidence: 99%
“…This rich diversity of elements which can be incorporated into the TTB structure allows for compositional tuning that has been exploited for development of new phases [13,19] ranging from ferroelectrics [20][21][22] to microwave dielectrics [23,24] and to ionic conductors [25]. During the last few years, the research dedicated to novel TTB ferroelectric and ferroelectric-related materials resurrected [15][16][17][18][19][20][21][22][26][27][28][29][30][31], with the Ba 6 FeNb 9 O 30 (BFNO) [32][33][34][35] as starting point. Earlier data reported that BFNO is ferroelectric with T C values either in the range 133-138 K [36] or 570-583 K [37,38], however being not electrically homogeneous [29] and with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3+ /Fe 2+ ); both low temperature dielectric spectroscopy and high temperature impedance spectroscopy measurements indicated more electroactive regions than anticipated [16].…”
Section: Introductionmentioning
confidence: 99%